The Effect of Strategic Intelligence, Effective Decision-making and Strategic Flexibility on Logistics Performance - Husam Mahmmud Jamil Abu Hamour; Jasser Abedelrazzaq Yacoub ALensou; Ahmad Nasser Abuzaid; Ahmad Fathi Alheet; Saif-aldeen Marwan Madadha; Murad Ali Ahmad Al-Zaqeba (Growing Science Ltd, 2024)
Indexed by Scopus